Parametric Excitation and Instabilities of Spin Waves Driven by Surface Acoustic Waves - Moritz Geilen; Roman Verba; Abbass Hamadeh; Alexandra Nicoloiu; Daniele Narducci; Adrian Dinescu; Milan Ender; Morteza Mohseni; Florin Ciubotaru; Mathias Weiler; Alexandru Müller; Burkard Hillebrands; et al. (Advanced Physics Research)
Abstract The parametric excitation of spin waves by coherent surface acoustic waves in metallic magnetic thin film structures is demonstrated experimentally using Brillouin light scattering spectroscopy. Complementary micromagnetic simulations and analytical modeling reveal that, depending on the experimental conditions, the spin‐wave instabilities originate from different phonon‐magnon and magnon‐magnon scattering processes. This opens novel ways to create micro‐scaled nonlinear magnonic systems for logic and data processing that profit from the efficient excitation of phonons using piezoelectricity.